Martin Luther: An Open Letter on Translating, translated by Howard Jones - Jones, H (Taylor Institution Library, 2017)
The Open Letter on Translation is a seminal document in German literature, translation studies, and Reformation theology. This new translation aims to bring Martin Luther's irreverent and brilliant rhetoric to life for the modern reader, as the great practitioner explains his methods and principles.